The Importance of Iron: : Anemia Counseling to Maintain Energy Stability and Concentration at SMKN Palang, Tuban Regency - Ahmad David Royyifi Arifin; Lilia Fariaftul Fauziah; Nikita Welandha Prasiwi (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Iron plays a crucial role in the formation of hemoglobin, which carries oxygen throughout the body. Iron deficiency, causing anemia in teenagers, can result in fatigue, decreased concentration, and even decreased immunity. The prevalence of anemia in Indonesia is high, especially among adolescent girls. Anemia can affect study concentration and productivity. Adolescents' learning concentration is influenced by various factors, including insufficient iron intake. Therefore, this counseling aims to increase understanding of the importance of iron in maintaining energy balance and concentration at school, reducing the impact of anemia on adolescent well-being. These extension activities apply an educational and preventive approach. By providing clear information about the role of iron, the consequences of deficiency, and the impact of anemia, an educational approach is used to increase students' understanding. Anemia education has succeeded in increasing students' understanding of the causes, symptoms, impacts and prevention of anemia. The students' active participation during the session marked a high level of engagement. The conclusion shows that this activity not only provides knowledge, but also increases students' awareness of the link between their health and academic achievement.